2016
DOI: 10.1017/jfm.2016.210
|View full text |Cite
|
Sign up to set email alerts
|

Transient growth of perturbations in Stokes oscillatory flows

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. Oscillatory Stokes flows, with zero mean, are subjected to subcritical transition to turbulence. The maximal energy growth of perturbations is computed in the subcritical regime through an optimisation method. The results show strong amplifications during half a period. The energy transfer from the base flow involves an Orr mechanism with two-dimensional vortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 29 publications
6
24
0
Order By: Relevance
“…Nebauer (2019) anticipated that in certain regimes of pulsatile pipe flow, the energy growth scales exponentially with the Reynolds number. This was also reported for the oscillatory Stokes layer over a flat plate (Biau 2016) and for the flow following an axisymmetric stenosis (Blackburn, Sherwin & Barkley 2008). Large non-modal transient amplification of disturbances has also been found in pulsatile channel flow (Tsigklifis & Lucey 2017).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Nebauer (2019) anticipated that in certain regimes of pulsatile pipe flow, the energy growth scales exponentially with the Reynolds number. This was also reported for the oscillatory Stokes layer over a flat plate (Biau 2016) and for the flow following an axisymmetric stenosis (Blackburn, Sherwin & Barkley 2008). Large non-modal transient amplification of disturbances has also been found in pulsatile channel flow (Tsigklifis & Lucey 2017).…”
Section: Introductionsupporting
confidence: 68%
“…However, approximately of the kinetic energy is shared in equal parts between the azimuthal and stream-wise components, which indicates a strong three-dimensional effect, distinct from the two-dimensional Orr mechanism reported for many flows (see e.g. Boyd 1983; Farrell 1988; Maretzke, Hof & Avila 2014; Biau 2016).…”
Section: Dynamics Of the Optimal Disturbancementioning
confidence: 72%
“…This would imply that the finite amplitude instability can be triggered very easily in both experiments by ambient noise and numerical simulations by the supposedly small initial conditions used to initiate runs (Ozdemir et al 2014). The linear nonmodal analysis also indicates that only the Orr mechanism is important and so the optimal starting time found there may be good for the nonlinear nonmodal analysis too: see Table 1 of Biau (2016).…”
Section: Time-periodicmentioning
confidence: 98%
“…This exponential growth of the maximum amplification with the Reynolds number has also been observed for other flows displaying an adverse pressure gradient. For example, Biau (2016) observed that the maximum amplification of two-dimensional perturbations for Stokes' second problem grows exponentially with the Reynolds number. In the following, we shall see that the competition of the maximum amplification between the quadratic growth in Re δ of streamwise streaks, equation (3.5), and the exponential growth in Re δ of two-dimensional structures, equation (3.20), composes the essential primary instability mechanism of this flow.…”
Section: Theoretical Considerationsmentioning
confidence: 99%